Lachnoanaerobaculum orale bacteremia in a patient with acute myeloid leukemia and stomatitis: An emerging pathogen - Nasruddin Ali Salad Sabrie; Sheliza Halani; Finlay Maguire; Patryk Aftanas; Robert Kozak; Nisha Andany (IDCases, 2023)
Background: Lachnoanaerobaculum orale is a newly described, obligately anaerobic gram-positive bacillus. The first report of invasive disease caused by L. orale was described in a patient with acute lymphocytic leukemia following systematic chemotherapy. Here we describe another case of L. orale bacteremia in a patient with a hematologic malignancy following chemotherapy-induced neutropenia. Methods: We present a case of a 46-year-old woman with a recent diagnosis of AML who presented to Sunnybrook Health Sciences Center with febrile neutropenia following induction chemotherapy with daunorubicin-cytarabine (3 +7 regimen) with Gemtuzumab and Ozogamycin. Despite being on intravenous pipercillin-tazobactam she remained febrile. Following our clinical assessment and investigations, potential sources of infection included a swollen digit and severe mucositis. Results: One blood culture from admission grew Lachnoanaerobaculum orale in the anaerobic bottle, identified by Matrix-Assisted Laser Desorption Ionization-Time of Flight (MALDI-TOF). The isolate also underwent whole-genome sequencing using methods that have been described previously. Results demonstrated the organism was susceptible to cefoxitin, clindamycin, meropenem, metronidazole, penicillin, and piperacillin-tazobactam. We concluded that the source of this patient’s bloodstream infection to be chemotherapy-induced stomatitis. Conclusion: With the increasing use of intensive immunosuppressive regimens and hematopoietic stem cell transplantation for patients with hematologic malignancies, there has been an increase in the incidence and detection of bloodstream infections due to anaerobic organisms. This is only the second case report of L. orale bacteremia, highlighting its emerging role as an opportunistic pathogen in immunocompromised patients.